Pengaruh Komunikasi, Konflik Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Sekar Ayu Kediri - Ramadhinik Nanda Putri; Indah Yuni Astuti; Endah Kurniawati (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the influence of communication, conflict and work discipline on employee performance. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to 30 Sekar Ayu Kediri employees and calculated using the SPSS Version 25 application. Data analysis techniques used included Validity Test, Reliability Test, Classic Assumption Test (Normality Test, Multicollinearity, Heteroscedasticity , Linearity), Multiple Linear Regression Analysis, t Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it is known that all question items (X1, X2, Then in the reliability test, it is known that the Cronbach Alpha value is > 0.60 so that the indicators for each question are declared reliable. In the t test it is known that all items have a positive value and <0.05 so that all items (Communication, Conflict, Work Discipline) have a partial effect on employee performance. Furthermore, in the F test it is known that the value of Sig. for all items together it is 0.000 < 0.05 so that all items are declared to have a simultaneous effect on employee performance. The final test, namely the R2 Coefficient of Determination Test, shows a result of 95.2%, which means that the variables of communication, conflict and work discipline can really influence employee performance and with this result it can be said that this research is successful because it has an Rsquare value > 50%.